Disability and health-related quality of life are associated with restricted social participation in young adults with juvenile idiopathic arthritis. (4th March 2019) - Rebane, K; Ristolainen, L; Relas, H; Orenius, T; Kautiainen, H; Luosujärvi, R; Aalto, K; Säilä, H
Abstract : Objectives : To describe a cohort of Finnish juvenile idiopathic arthritis (JIA) patients, to recognize those young adults who are at risk of becoming socially restricted by their long-term rheumatic disease, and to assess which areas of self-rated health-related quality of life (HRQoL) are associated with the emergence of restricted social participation. Methods : A total of 195 young adults with JIA completed questionnaires addressing demographics, health behaviour, physical activity, functional ability, HRQoL, depressive symptoms, and self-esteem. Patients were classified as having non-restricted social participation if they were engaged in studying, working, maternity leave, or military service, and restricted social participation if they were unemployed or on disability pension. Results : Of the patients, 162 (83%) were considered as having non-restricted social participation and 33 (16%) restricted social participation. Among patients with restricted social participation, five (15%) were on disability pension and 28 (85%) were unemployed. Patients with restricted social participation participated less in leisure-time non-physical activities (p = 0.033), felt more disturbed during their leisure time (p = 0.010), had lower self-esteem (p = 0.005), and had higher disability scores (p = 0.024). HRQoL scores revealed statistically significant differences between the groups: physical functioning (p = 0.043), social functioning (p = 0.016), and emotional well-being (p = 0.049) were all lower in patients with restricted social participation. Conclusions : Socially restricted patients showed a higher degree of disability, and lower levels of physical functioning, self-esteem, emotional well-being, and social functioning. These patients should be recognized earlier and interventions provided to enhance their social participation.